THE MANAGER'S "PUZZLE": : HOW TO ORGANIZE MULTIDISCIPLINARY TEAMS - Cristina Gularte Liberato , Carla (Health and Society, 2021)
Working in multidisciplinary teams is important to provide quality care and excellence, a goal of practically all hospital units. Providing conditions for the development of this work, ensuring the well-being of the members of these teams, planning the forms of action, costs and investments are objectives of excellent management. For the objectives to become a reality, the manager must have knowledge of the actions developed in his unit, as well as conduct adequate and continuous training, supporting his team, resolving doubts, based on scientific evidence.